Pengembangan LKPD Berbasis Cerita Bergambar Digital Pada Siswa Kelas IV SD - Amelia, Delora Jantung; Muzakki, Abdurrohman (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
Abstract: Based on the needs analysis carried out by the researchers at SDN Gadingkulon II, researchers obtained information that students had difficulty understanding material during the pandemic, students were also less enthusiastic about carrying out online learning, students were late in collecting and doing assignments. This is because the material provided is in the form of documents in the form of pdf, doc and Power Point. Questions given through the googleform platform. With these problems, learning activities during the pandemic cannot run well. Therefore, the problems that exist in the field must be addressed immediately. From the problems above, it can be overcome by developing LPDD based on digital picture stories. The purpose of this research is to develop LKPD teaching materials based on picture stories that can be used as an alternative to teaching materials used during the COVID-19 pandemic that are feasible, practical and effective and in accordance with the characteristics of students. This study uses the ADDIE development model which consists of five steps: Analyze (analyze), Design (design), Develop (development), Implementation (implementation), and Evaluation (evaluation). The subjects of this study were 4th grade students. The data collection techniques in this study were observation, interviews, questionnaires and documentation. The final result of the research shows that the validation results can be said to be feasible where the validation results from material experts get a validity level of 85.5% of these results have entered the valid or feasible type. which of these results can also be said to be valid or feasible to be tested. Keywords: Teaching materials, picture stories.